Multiple Choice Which equation is equivalent to y – 6 = –12(x + 4)? (1 point) Responses y = –6x – 48 y = –6 x – 48 y = 6x – 48 y = 6 x – 48 y = –12x – 42 y = –12 x – 42 y = –12x – 54

1 answer

The equation y – 6 = –12(x + 4) can be simplified by distributing -12 to (x+4):

y - 6 = -12x - 48

Then, by rearranging the terms, we can arrive at the equation in one of the answer choices:

y = -12x - 48 + 6

Which simplifies to:

y = -12x - 42

Therefore, the correct answer choice is:

y = -12x - 42
Similar Questions
  1. Multiple ChoiceWhich expression is equivalent to (–2)(a + 6)? (1 point) Responses –2a + 6 –2 a + 6 2a + 12 2 a + 12 –2a
    1. answers icon 33 answers
    1. answers icon 1 answer
  2. Multiple ChoiceWhich of the following is a solution to the equation y = 3x – 1? (1 point)
    1. answers icon 21 answers
  3. Multiple ChoiceIs (0, 3) a solution to the equation y = x + 3? (1 point) Responses yes yes no no
    1. answers icon 12 answers
more similar questions